Differential Responses of Tragus biflorus Schult to N : P : K - Singh, V. P.; Upadhyaya, S. D. (Indian Forester, 1977)
The fertilizer treatment of N, P and K individually and at different combinations on the morphology, reproductive capacity and biomass production exhibit that combined effect of N : P : K is most effective for the maximum development of the above mentioned parameters.